Implementasi Nilai-Nilai Akhlak dalam Kitab Ta’lim Muta’alim di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Fitria Fatmawati; Yuli Habibatul Imamah; Etika Pujianti (Journal on Education, 2024)
This examination plans to depict how the virtues in the Ta'limu book are executed in the Hidayatul Mubtadiin Islamic Live-in School, Jati Agung, South Lampung and what are the supporting and hindering elements in carrying out the virtues in the Ta'lim Muta'alim Islamic Life experience School in the Islamic All inclusive School. Hidayatul Mubtadiin Jati Agung, South Lampung. This sort of examination is field research. The idea of this examination is subjective engaging exploration. The information assortment procedure is perception, meetings and documentation. Testing the legitimacy of the information utilizing triangulation. In the mean time, information examination utilizes information decrease, introducing information and reaching determinations. The consequences of this examination show the execution of virtues in the book Ta'limu Muta'alim at the Hidayatul Mubtadiin Islamic live-in school, in particular. Among the types of extolling information that should be done isn't to extend your feet towards the book, put the book of understanding on top of different books, and don't put something on the book (like ink and different things. Among the types of regard for a science master/educator is regarding his youngsters and any individual who has a relationship with him. In the mean time, the supporting elements and repressing variables come from offices and foundation, understudies, ustadz/ustadzah, and furthermore the strategy utilized.